A LICENÇA CREATIVE COMMONS E A COMUNICAÇÃO CIENTÍFICA: a questão dos periódicos eletrônicos de acesso aberto - Oliveira, Flasleandro Vieira de (2011)
Scientific communication is the pr erequisite to accomplish any scientific activity. The Open Access Movement for scientific communication, offers different practices from the traditional way of communicating scientific knowledge, in reference to the access to periodical publications with expensive subscription. Copyright (authors rights) has been the biggest barrier to the Open Access Movement improvement. The use of licenses as possibility for a more flexible use of copyrighted literature allowing a greater sharing of scientific information is discussed. Among existing licenses, the Creative Commons are the main object of this research. The Creative Commons is widespread both nationally and internationally as an instrument to make access and extended use of intellectual works easier. Based on this perspective, this research aimed at investigating the benefits that the adoption of such licenses may bring to the dissemination of scientific information sharing as far as the free access to electronic magazines is concerned. With this purpose, the Scientific Electronic Library On line (SciELO) was the chosen object, through the selection of some scientific journals as samples from different fields of knowledge. The methodological procedure was based on the application of questionnaires to authors and editors of the selected periodicals, aiming at obtaining some elements in order to investigate how important the Creative Commons in the Open Access Movement are in the point of view of the referred actors